Polar, arctic, northern: Corpora-based study of the semantics of relative adjectives in language - Vinogradova, Svetlana A.; Abramzon, Tatiana Ye.; Dorozhkin, Andrey G.; Savateeva, Oxana V.; Ganitch, Elena S.; Pedko, Vitalii A. (Universidade Estadual Paulista, 2022)
The adjectives ‘northern’, ‘polar’ and ‘arctic’ are subjected to multilateral analysis of their etymology, frequency, semantic development and current usage in language. The article reveals the common specific semantic features of the English denominal adjectives on the material of these three adjectives. A comprehensive semantic-cognitive analysis was performed summarizing the conclusions obtained in the framework of the definitional analysis, contextual analysis, diachronic analysis of the transformations of linguistic meanings and their cognitive interpretation. The results show active development of the semantic structures, relative growth of metonymic meanings, extension of metaphorical uses. The adjective ‘northern’ displays the highest number of uses due to its native origin, early appearance in the English vocabulary, a big number of bound meanings in terminological or phraseological usages, and the existence of metaphorical meaning. Los adjetivos 'norte', 'polar' y 'ártico' se someten a un análisis multilateral de su etimología, frecuencia, desarrollo semántico y uso actual en el lenguaje. El artículo revela las características semánticas específicas comunes de los adjetivos denominacionales en inglés sobre el material de estos tres adjetivos. Se realizó un análisis semántico-cognitivo integral que resumió las conclusiones obtenidas en el marco del análisis definicional, análisis contextual, análisis diacrónico de las transformaciones de significados lingüísticos y su interpretación cognitiva. Los resultados muestran un desarrollo activo de las estructuras semánticas, crecimiento relativo de los significados metonímicos, extensión de los usos metafóricos. El adjetivo ‘northern’ presenta el mayor número de usos debido a su origen nativo, aparición temprana en el vocabulario inglés, gran cantidad de significados ligados en usos terminológicos o fraseológicos, y la existencia de significado metafórico. Os adjetivos ‘norte’, ‘polar’ e ‘ártico’ são submetidos à análise multilateral de sua etimologia, ...